The Inhibition of B7H3 by 2-HG Accumulation Is Associated With Downregulation of VEGFA in IDH Mutated Gliomas - Zhang, Mengli; Zhang, Huaichao; Fu, Minjie; Zhang, Jingwen; Zhang, Cheng; Lv, Yingying; Fan, Fengfeng; Zhang, Jinsen; Xu, Hao; Ye, Dan; Yang, Hui; Hua, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
B7H3 (also known as CD276) is a co-stimulator checkpoint protein of the cell surface B7 superfamily. Recently, the function beyond immune regulation of B7H3 has been widely studied. However, the expression preference and the regulation mechanism underlying B7H3 in different subtypes of gliomas is rarely understood. We show here that B7H3 expression is significantly decreased in IDH-mutated gliomas and in cultured IDH1-R132H glioma cells. Accumulation of 2-HG leads to a remarkable downregulation of B7H3 protein and the activity of IDH1-R132H mutant is responsible for B7H3 reduction in glioma cells. Inhibition of autophagy by inhibitors like leupeptin, chloroquine (CQ), and Bafilomycin A1 (Baf-A1) blocks the degradation of B7H3 in glioma cells. In the meantime, the autophagy flux is more active with higher LC3B-II and lower p62 in IDH1-R132H glioma cells than in IDH1-WT cells. Furthermore, sequence alignment analysis reveals potential LC3-interacting region (LIR) motifs ‘F-V-S/N-I/V’ in B7H3. Moreover, B7H3 interacts with p62 and CQ treatment significantly enhances this interaction. Additionally, we find that B7H3 is positively correlated with VEGFA and MMP2 by bioinformatics analysis in gliomas. B7H3 and VEGFA are decreased in IDH-mutated gliomas and further reduced in 2-HGhigh gliomas compared to 2-HGlow glioma sections by IHC staining. Our study demonstrates that B7H3 is preferentially overexpressed in IDH wild-type gliomas and could serve as a potential theranostic target for the precise treatment of glioma patients with wild-type IDH.